RELIABILITY OF RSA ALGORITHM AND ITS COMPUTATIONAL COMPLEXITY - Karpinskyy, Mykola; Kinakh, Yaroslav (International Journal of Computing, 2014)
This article deals with the RSA encryption algorithm. Its safety is analyzed using the number field sieve method. The algorithm work results allow to define a define a secret key in a simple way.